Factors influencing the kinetics of MSU crystal depletion measured with dual-energy CT in patients with gout - Tristan Pascart; Victor Laurent; Charlotte Jauffret; Aurore Pacaud; Vincent Ducoulombier; Julie Legrand; Stéphane Verdun; Laurène Norberciak; Jean-François Budzik (RMD Open)
Objective To examine factors influencing the kinetics of monosodium urate (MSU) crystal dissolution measured with dual-energy computed tomography (DECT) during follow-up of patients with gout.Methods Patients with a diagnosis of gout with baseline knees and feet DECT scans exhibiting MSU crystal volumes ≥0.1 cm3 and at least one follow-up DECT were included. Spearman’s correlation coefficient was used to search for association between change from baseline MSU crystal volume at 6, 12, 18 and 24 months and serum urate (SU) level. Associations between percentage change from the baseline volume of MSU crystal deposits and explanatory variables were assessed using linear mixed models.Results Sixty-two patients (age 67.3±12.8 years; 53 (85%) males) cumulating 104 follow-up DECT scans were included. Overall, SU target levels (<6.0 and <5.0 mg/dL) were achieved by 48 (77%) and 36 (58%) patients, respectively. There was a good correlation (r=0.66; p<0.0001) observed between SU level and percentage change in MSU crystal volume. The median decrease from baseline MSU crystal volume was greater in patients reaching the <5.0 mg/dL SU target than in those reaching ≥5.0 SU <6.0 mg/dL: −85% (95% CI: −94% to −72%) versus −40% (−57% to −22%; p<0.05) at 12 months. In multivariable analysis, time (in days) with a multilevel coefficient of −0.06 (95% CI: −0.08 to −0.03, p<0.001), hypertension (coefficient: 41.87, 95% CI: 16.38 to 67.18, p<0.01) and SU level <5.0 mg/dL (coefficient: −39.46, 95% CI: −70.93 to −8.34, p=0.02) were the only variables significantly associated with MSU crystal volume change.Conclusion In patients with DECT-measured MSU crystal deposition, reaching the <5.0 mg/dL SU target provides more extensive and rapid crystal dissolution than reaching the <6.0 mg/dL SU target.